Polyamines as redox homeostasis regulators during salt stress in plants - Saha, Jayita; Brauer, Elizabeth K.; Sengupta, Atreyee; Popescu, Sorina C.; Gupta, Kamala; Gupta, Bhaskar (Frontiers in Environmental Science, 2015)
The balance between accumulation of stress-induced polyamines and reactive oxygen species (ROS) is arguably a critical factor in plant tolerance to salt stress. Polyamines are compounds, which accumulate in plants under salt stress and help maintain cellular ROS homeostasis. In this review we first outline the role of polyamines in mediating salt stress responses through their modulation of redox homeostasis. The two proposed roles of polyamines in regulating ROS – as antioxidative molecules and source of ROS synthesis – are discussed and exemplified with recent studies. Second, the proposed function of polyamines as modulators of ion transport is discussed in the context of plant salt stress. Finally, we highlight the apparent connection between polyamine accumulation and programmed cell death induction during stress. Thus polyamines have a complex functional role in regulating cellular signaling and metabolism during stress. By focusing future efforts on how polyamine accumulation and turnover is regulated, research in this area may provide novel targets for developing stress tolerance.